Prognosis of Patients with Sepsis and Non-Hepatic Hyperammonemia: A Cohort Study - Zhao, Lina (Med Sci Monit, 2020)
BACKGROUND: Hyperammonemia has been reported in some critically ill patients with sepsis who do not have hepatic failure. A significant proportion of patients with non-hepatic hyperammonemia have underlying sepsis, but the association between non-hepatic hyperammonemia and prognosis is unclear. MATERIAL/METHODS: Information about patients with sepsis and non-hepatic hyperammonemia was retrieved from the Medical Information Mart for Intensive Care-III database. Survival rates were analyzed using the Kaplan-Meier method. Multivariate logistic regression models were employed to identify prognostic factors. Receiver operating characteristic (ROC) curve analysis was used to measure the predictive ability of ammonia in terms of patient mortality. RESULTS: A total of 265 patients with sepsis were enrolled in this study. Compared with the non-hyperammonemia group, the patients with hyperammonemia had significantly higher rates of hospital (59.8% vs. 43.0%, P=0.007), 30-day (47.7% vs. 34.8%, P=0.036), 90-day (61.7% vs. 43.7%, P=0.004), and 1-year mortality (67.3% vs. 49.4%, P=0.004). In the survival analysis, hyperammonemia was associated with these outcomes. Serum ammonia level was an independent predictor of hospital mortality. The area under the ROC curve for the ammonia levels had poor discriminative capacity. The hyperammonemia group also had significantly lower Glasgow Coma Scale scores (P=0.020) and higher incidences of delirium (15.9% vs. 8.2%, P=0.034) and encephalopathy (37.4% vs. 19.6%, P=0.001). Intestinal infection and urinary tract infection with organisms such as Escherichia coli may be risk factors for hyperammonemia in patients who have sepsis. CONCLUSIONS: Higher ammonia levels are associated with poorer prognosis in patients with sepsis. Ammonia also may be associated with sepsis-associated encephalopathy. Therefore, we recommend that serum ammonia levels be measured in patients who are suspected of having sepsis.